2015
DOI: 10.3791/53074
|View full text |Cite
|
Sign up to set email alerts
|

Determining Ultrasonic Vocalization Preferences in Mice using a Two-choice Playback Test

Abstract: Mice emit ultrasonic vocalizations (USVs) during a variety of conditions, such as pup isolation and adult social interactions. These USVs differ with age, sex, condition, and genetic background of the emitting animal. Although many studies have characterized these differences, whether receiver mice can discriminate among objectively different USVs and show preferences for particular sound traits remains to be elucidated. To determine whether mice can discriminate between different characteristics of USVs, a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Few studies have explored the receiver's side 30 37 38 . Playback and discrimination protocols provide a simple test to study the receiver's side, such as the one also recently described by Asaba, Kato, et al 39 . In that study, the authors used a two-choice test box separated with acoustic foam instead of the Y-maze box described here.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have explored the receiver's side 30 37 38 . Playback and discrimination protocols provide a simple test to study the receiver's side, such as the one also recently described by Asaba, Kato, et al 39 . In that study, the authors used a two-choice test box separated with acoustic foam instead of the Y-maze box described here.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for USV measurement were performed, as described previously (Asaba et al, 2015;Asaba et al, 2014).…”
Section: Measurement Of Usvsmentioning
confidence: 99%
“…These vocalizations are strongly modulated on different levels by a variety of contextual determinants, such as age, genetic background, behavioural state and to a lesser extent by sex 5 . Mice utilize these USVs during social interactions and in distress to mediate essential behaviours 6 12 . Recently, it has been shown that playback of different types of USVs can also elicit different responses in the recipient mouse 13 .…”
Section: Introductionmentioning
confidence: 99%